EVALUASI SISTEM PENGENDALIAN MANAJEMEN UNTUK PUSAT TANGGUNG JAWAB LABA PADA CV AKE ABADI KECAMATAN AIRMADIDI - Ering, Windy Fieska; Saerang, David P.E; Tirajoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
CV. Ake Abadi is a company engaged mineral drinking water supply , in doing good management control will facillitate the application of accounting accountability within then company so that the company?s goals can be achieved. With the right management control systems,the management in organizations the company can evaluate the results of an operation or an activity is running efficiently and effectively. The purpose of this study was to determine the management control system to profit center responsibility Ake Abadi CV. The analytical method used is descriptive analysis . The analysis showed that the control of profit center manager at CV Ake Abadi has met one of the characteristics of accounting that is the identification of accountability profit centers. Implementation of central management control accountability in the CV Ake Abadi earnings are sufficient, it can be seen from the registration and authorization for expenditure costs and the calculation of an adequate financial statement analysis, and can be used as a management tool in controlling the profit center as a means of controlling costs.